2003
DOI: 10.1007/s00442-003-1267-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenological variation as protection against defoliating insects: the case of Quercus robur and Operophtera brumata

Abstract: Phenological synchrony between budburst and emergence of larvae is critical for the fitness of many spring-feeding insect herbivores. Therefore, large intraspecific variation in timing of budburst of the host may have a negative effect on the herbivore. We studied how asynchrony between emergence of larvae and budburst affects the fitness of Operophtera brumata (Lepidoptera: Geometridae), a major defoliator of Quercus robur, which can adapt to the phenology of a single tree. It is known that, in maturing leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 36 publications
6
110
1
1
Order By: Relevance
“…To evaluate the risk quantitatively, we combined host specificity tests and garden rearing data with the evaluation of ecological field data on relative phenology, suggested as important by the retrospective studies summarized above, to prospectively evaluate the likelihood and magnitude of the potential interaction of R. conicus with C. pitcheri . While phenology is recognized as important in insect-plant interactions (e.g., Russell and Louda, 2004;Tikkanen and Julkunen-Tiitto, 2003), we found no prior studies that quantified the degree of likely phenological synchrony between a biocontrol agent and a potential secondary host plant species prior to contact.…”
Section: Intraguild Indirect Interactions With Native Floral Herbivorescontrasting
confidence: 46%
“…To evaluate the risk quantitatively, we combined host specificity tests and garden rearing data with the evaluation of ecological field data on relative phenology, suggested as important by the retrospective studies summarized above, to prospectively evaluate the likelihood and magnitude of the potential interaction of R. conicus with C. pitcheri . While phenology is recognized as important in insect-plant interactions (e.g., Russell and Louda, 2004;Tikkanen and Julkunen-Tiitto, 2003), we found no prior studies that quantified the degree of likely phenological synchrony between a biocontrol agent and a potential secondary host plant species prior to contact.…”
Section: Intraguild Indirect Interactions With Native Floral Herbivorescontrasting
confidence: 46%
“…Our results suggested that these selection pressures were acting on the same genomic regions through mechanisms able to maintain diversity over long evolutionary times (balancing, disruptive, or frequency-dependent selection). At least in oaks, it has been shown that coevolution of defoliating insects and oaks may be responsible for wide within-population variation of bud burst (Tikkanen and Tiitto 2003). Maintenance of a high level of heterozygote loci would fit well with the hypothesis of a phenotypic plasticity mainly based on allelic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…For many defoliators of temperate forests synchrony in phenology between budburst and larval development is determinant to growth and survival of these defoliators [83,91,92]. A good synchronization between hatching and budburst allows larvae to feed on soft and young foliage, with high food quality [5,30,36]; see also indirect effects).…”
Section: Impacts On Insect Phenology In Interaction With Host Phenologymentioning
confidence: 99%
“…For geometrids, generalist defoliators of broadleaf trees such as O. brumata, larvae feeding on ageing foliage show declining growth rates and increasing dispersal with a dramatic increase in mortality since this dispersal is passive [19,82,83]. Consequently, a differential effect of warmer temperatures on budburst and larval phenology would have marked effects on the abundance of this species in extreme years such as 2003.…”
Section: Impacts On Insect Phenology In Interaction With Host Phenologymentioning
confidence: 99%